2014
DOI: 10.3389/fped.2014.00077
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Manifestations of Primary Immunodeficiency Disorders in Children

Abstract: Primary immunodeficiencies (PIDs) are inherited disorders in which one or several components of immune system are decreased, missing, or of non-appropriate function. These diseases affect the development, function, or morphology of the immune system. The group of PID comprises more than 200 different disorders and syndromes and the number of newly recognized and revealed deficiencies is still increasing. Their clinical presentation and complications depend on the type of defects and there is a great variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 80 publications
2
76
0
7
Order By: Relevance
“…These complications comprise a wide range of infectious conditions (eg, bronchitis, pneumonia, empyema, and lung abscess) and noninfectious conditions (eg, hilar/mediastinal adenopathies, and obstructive and restrictive lung diseases) [46,47]. The development of noninfectious manifestations of the lower respiratory tract is usually multifactorial owing to immune dysregulation (eg, chronic inflammation, autoimmunity, and allergy), adverse effects of therapies, and malignancies [8]. Lower respiratory tract complications are examined in the following sections.…”
Section: Lower Respiratory Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…These complications comprise a wide range of infectious conditions (eg, bronchitis, pneumonia, empyema, and lung abscess) and noninfectious conditions (eg, hilar/mediastinal adenopathies, and obstructive and restrictive lung diseases) [46,47]. The development of noninfectious manifestations of the lower respiratory tract is usually multifactorial owing to immune dysregulation (eg, chronic inflammation, autoimmunity, and allergy), adverse effects of therapies, and malignancies [8]. Lower respiratory tract complications are examined in the following sections.…”
Section: Lower Respiratory Tractmentioning
confidence: 99%
“…The spectrum of respiratory manifestations is extremely wide, including acute and chronic infections (eg, recurrent, severe, persistent infections affecting various locations, and opportunistic or unusual pathogens), immune dysregulation (eg, autoimmunity, allergy, and lymphoproliferative disorders), structural abnormalities, and malignancies. As survival from infection improves (mortality from PID is still 30%-45% worldwide), noninfectious pulmonary complications are more frequently observed among patients with PIDs [8,9]. Standard management of the respiratory complications of PID is complemented by more specific therapeutic modalities, including surgery (otitis, sinusitis, adenoiditis, and lung infection), lung transplantation, and symptomatic therapies (anti-inflammatory drugs, mucolytics, bronchodilators, and inhalers).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, infections were the most common sinopulmonary manifestations in our cohort, which is consistent with previous reports. 29 In a previous study, 14% of the subjects who presented with recurrent pneumonia were found to have an underlying immune disorder. 30 Because respiratory infections are common in general, physicians should be alerted about the proper indications to work up patients for the possibility of primary immunodeficiency disorders.…”
Section: Discussionmentioning
confidence: 93%
“…As observed in our cohort, the pathogens that cause respiratory infectious complications in primary immunodeficiency disorder display a typical spectrum according to the immune defect. 29 This observation should aid in the diagnostic approach in an attempt to identify a particular type of primary immunodeficiency disorder. For example, patients with combined immunodeficiencies are prone to develop respiratory infections caused by a wide range of bacteria, fungi, and viruses, whereas patients with predominantly antibody deficiencies are at risk of developing bacterial respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, these diseases are not as rare as originally suspected. The spectrum of PID disorders has greatly widened in the past few decades, with more than 200 different disorders or syndromes, affecting the immune system development, function, or morphology (1,2). It is well accepted that clinical presentations of PID disorders are highly variable and include inflammatory, autoimmune, allergic, and lymphoproliferative symptoms, as well as susceptibility to recurrent infections, which is the hallmark of these disorders (3,4).…”
Section: Introductionmentioning
confidence: 99%